EBV IN HODGKIN LYMPHOMA - Giuseppina Massini; Doerte Siemer; Stefan Hohaus (Mediterranean Journal of Hematology and Infectious Diseases)
Up to 40% of Hodgkin lymphoma (HL) cases are associated with the Epstein-Barr virus (EBV). Clonal viral genomes can be found in the HL tumor cells, the Hodgkin Reed-Sternberg cells (HRS). The latent infection results in expression of the viral oncogenes LMP1 and LMP2A which contribute to generate the particular phenotype of the HRS cells. EBV does not only undergo epigenetic changes of its genome during latency, but also induces epigenetic changes in the host genome. The presence of EBV may alter the composition and activity of the immune cells surrounding the HRS cells. EBV favours a  Th1 reaction, but this attempt at a cell mediated immune response appears to be ineffective. The presence of EBV in HL is associated with several clinicopathological characteristics: It is more frequent in cases with mixed cellular histology, in males, in children and older adults, and in developing countries, while the young-adult onset HL of nodular sclerosis type in industrialized countries is typically EBV-negative. Countries in the Mediterranean area often show  an intermediate epidemiological pattern. Recent studies suggest a genetic predisposition to develop EBV-associated HL. Circulating EBV-DNA may serve as a biomarker to monitor response to therapy, and eventually, EBV will become a target for therapeutic intervention also in HL.